Genitourinary Blastomycosis in a Young Male Patient: A Case Report and Review of Diagnostic Challenges - Emily Hillman; Hangcheng Fu; Randa Obid; Uzoma A. Anele (Case Reports in Infectious Diseases)
Disseminated blastomycosis is an endemic fungal infection that rarely manifests with genitourinary involvement. We present a unique case of a 28-year-old professional male gamer with a remote history of hemoptysis and cervical lymphadenopathy who presented with hematospermia, lower urinary tract symptoms (LUTS), and persistent groin abscesses after left orchiectomy at an outside hospital. He underwent drainage of groin abscess and prostate biopsy for an abnormal digital rectal exam which revealed disseminated blastomycosis requiring systemic, long-term antifungal treatment. We have also included a review of literature to note clinical patterns in presentations and highlight the diagnostic challenges that this infection presents.